Overload pain but root differentiation discomfort in the lumbar spine - Siminska, Joanna; Nowacka, Krystyna; Siedlecki, Zygmunt; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
Lumbar pain syndromes of the spine can also be referred to as the pain of the cross. These ailments have now become epidemics of our time. In literature, these pain are referred to as localized ailments that are located in the lumbar, lumbosacral, and cross-iliac areas. Cross pains are a very general term because there are a multitude of factors that cause lumbar disc herniation. This problem poses great diagnostic difficulties. [4]. The nature of these ailments is often difficult to pinpoint by the patient, but it can be the pain that describes patients from blunt, piercing, biting, baking, to those that are termed cold feeling. Keep in mind that the location of the lumbar pain symptoms varies. Patients report pain that is located throughout the lumbar-sacral area or only on one side of the spine, or occurs only in the area of the hip joints. These complaints often radiate along the lower limb. They are often the result of a lack of proper spine prevention: they contribute to this poor body posture, improper sleep positioning, as well as lack of coping skills, as well as a bad diet. In daily life, it is important to remember to do your daily activities in the correct position as well as to use prevention to avoid pain in the lumbar area.